Factors that influence the Islamic Perspective Human Development Index as Evidence of the Development of the Muslim Community - Dwi Lestari; Nur Azlia Arumi (IAIN Syekh Nurjati Cirebon, 2024)
This study aims to analyze the relationship between macroeconomics and zakat on the Human Development Index (HDI) and the Islamic Human Development Index (I-HDI) using the maqāṣid al-sharī'ah theory approach. We also calculate I-HDI based on maqāṣid al-sharī'ah theory by combining material and non-material aspects and then compare between I-HDI and HDI. The indicators used in the calculation of I-HDI are indicators that are relevant and in accordance with the objectives of maqāṣid al-sharīʿah, so that I-HDI can give a general picture of the results of human development. By employing the dynamic panel regression two-step Generalized Method of Moments (GMM) the study finds that there is a significant difference and quite a large disparity between the results of the HDI and I-HDI, in 34 provinces of Indonesia. The study reveals that economic growth, health fiscal policy, and zakat have a positive effect both on HDI and I-HDI. Nevertheless, the education fiscal policy variable has a positive effect on I-HDI, and conversely, has a negative effect on HDI. This condition occurs because the target and strategy for absorption of the education budget are not optimally carried out by the government. This research suggests that in formulating budget policies, the government should not only focus on material elements but also non-material elements which are reflected in the I-HDI model.